KONSEP PERLINDUNGAN HUKUM BAGI TENAGA MEDIS DALAM PENANGANAN COVID 19 - Dyah Tri Handini (HUKUM PEMBANGUNAN EKONOMI, 2021)
This article aims to understand the concept of legal protection for medical personnel in handling COVID-19. The increase in the incidence of covid 19 has an impact on the workload experienced by medical personnel, causing a decrease in the immune system of medical personnel. Most people who think that covid 19 is just a conspiracy have an impact on reducing public awareness in preventing covid 19. People who lack awareness of the importance of the covid 19 protocol will result in medical personnel being more at risk of being exposed to and experiencing covid 19. The results of this article show that there has been legal protection for medical personnel in handling COVID-19, both criminal law protection and employment law. The conclusion of this article is that the aspect of legal protection for medical personnel is contained in the codeki, Law R1 NO 29 of 2004 concerning Medical Practice, especially Article 48 concerning Medical Secrets, Regulations of the Minister of Health of the Republic of Indonesia number 269 and 290 and the Ministry of Health of the Republic of Indonesia.Keywords: Legal Protection, Medical Personnel, Covid-19. Artikel ini bertujuan untuk megetahui konsep perlindungan hukum bagi tenaga medis dalam penanganan covdi 19. Peningkatan kejadian covid 19 berdampak pada beban kerja yang dialami oleh tenaga medis sehingga meyebabkan penurunan sistem imun pada tenaga medis. Kebanyakan masyarakat yang menganggap bahwa covid 19 hanyalah sebuah konspirasi berdampak pada berkurangnya kesadaran masyarakat dalam pencegahan covid 19. Masyarakat yang kurang kesadaran akan pentingnya protokol covid 19 akan mengakibatkan tenaga medis lebih berisiko terpapar dan mengalami covid 19. Hasil artikel ini menunjukkan bahwa telah adanya perlidungan hukum bagi tenaga medis dalam penanganan covid 19, baik perlindungan hukum pidana maupun hukum ketenagakerjaan.  Kesimpulan artikel ini bahwa aspek perlindungan hukum bagi tenaga medis tertuang pada kodeki, UU R1 NO 29 Tahun 2004 tentang Praktek Kedokteran, khususnya pasal 48 tentang Rahasia Kedokteran, Peraturan Menteri Kesehatan Republik Indonesia nomor 269 dan 290 serta Kemenkes RI.Kata Kunci: Perlindungan Hukum, Tenaga Medis, Covid-19